Impact of Climate Change on Urban Slum Dwellers in Bangladesh: A Case Study of Four Selected Slums in Dhaka City - Suraiya Yasmin (Archives of Current Research International, 2016)
Introduction: The climate in Bangladesh is changing and it is becoming more unpredictable every year. The nature of relationship between climate change and livelihood assets of urban poor was experimented by the study. Aims: To understand the dynamics of climate change of urban poor and assess their livelihood strategies to the effect of climate change. Study Design: The study was done by quantitative and qualitative survey. Place and Duration of Study: The study was conducted in the four slums of Dhaka city namely Korail, Sattala, Nakhalpara and South Begunbari to assess the impact of climate change on the livelihood of urban poor from July, 2014 to January 2015. Methodology: A combination of quantitative and qualitative research methods was followed for the study. Impacts of climate change were assessed purposively on three livelihood capitals namely financial, social and human. Stratified Random Sampling method was applied for questionnaire survey. The four slums were selected regarding location, type of structure, density and size. The workable sample size of household (HH) was determined to be 374 for four slums. This total Household was equally distributed among selected slums according to the household number of each slum. The distributed household sample size for Korail slum was 140, sattala 172, Nakhalpara 27 and south begunbari 35. 3 Key Informant Interview (KII) and 8 Case Study were conducted for qualitative research. Results: The results illustrate that the poor are more vulnerable to climate change effects due to their poor livelihood conditions like deficient social network, low income, illiteracy, etc. The study identifies that due to change in climate, the majority of respondents (94.1%) suffered illness in last one decade. During hazardous conditions in slum they are deprived of regular food. They have limited access to information. They face problems in their work and lose savings with decreasing income. Conclusion: The slum dwellers are enduring and combating with the daily livelihood problems and the adverse effect of climate change put them in to a difficult state.